Influence of phosphates in reduction of the aftertaste of steviol glycoside (derived from Stevia rebaudiana Bertoni) in black tea drinks. Issue 11 (1st September 2022) - da Silva, Fernanda Lopes; Pinto, Vinicius Rodrigues Arruda; de Souza, Louise Bergamin Athayde; Stephani, Rodrigo; Perrone, Ítalo Tuler; de Carvalho, Antônio Fernandes
Abstract: This study evaluated the effect of the addition of phosphates on the reduction of the aftertaste of steviol glycoside in black tea, through the methodology of hedonic thresholds. Initially, five phosphate salts were evaluated for their ability to reduce the aftertaste in three brands of commercial stevia. Stevia C and two phosphates (DSP and SPP) have been chosen from the results, because they showed the best results for the overall impression and the reduction of sweetness and bitterness, respectively. A blend of DSP and SPP was applied as a standard criterion. Finally, the compromised acceptance threshold (CAT) (2.81%) and hedonic rejection threshold (HRT) (0.054%) were determined. It was still possible to determine the HRT for the bitterness attribute in the value of 1.39%. The present study demonstrates that the use of phosphate allows the reduction of stevia aftertaste in black tea. Novelty Impact Statement: Sensory tests showed a reduction of stevia aftertaste by phosphate salts; certain phosphate salts are able to further reduce bitterness and other sweetness; the combined use of phosphate salts aids in better performance.